Educational resources and instructional approaches for Chinese Hua'er Folk Songs in Gansu and Ningxia - Wang, Xufeng; Chuangprakhon, Sayam; Jian, Shuying; Wang, Guangguo (Journal of Education and Learning (EduLearn), 2024)
This study delves into the cultural significance and educational potential of Hua'er folk songs within the Hui ethnic communities of Gansu and Ningxia in northwest China. By positioning Hua'er as an indispensable educational tool in folk song history, the research seeks to safeguard and elevate this revered musical tradition. Employing literature reviews, immersive fieldwork, questionnaire surveys, interviews with four significant contributors, and direct observations, the study sheds light on the importance of Hua'er music as a cultural legacy. These insights offer valuable guidance for educators, cultural institutions, and future research initiatives. Through a detailed exposition of the research methodology, this study enriches our understanding of the diverse landscape of Chinese folk song history, presenting avenues for further exploration and practical application in educational contexts.